Keterampilan Passing Bawah: Analisis Keterampilan Gerak Bola Voli pada Atlet Siswa: Keterampilan Passing Bawah: Analisis Keterampilan Gerak Bola Voli pada Atlet Siswa - Muhammad Khoiruddin Alvin, Alvin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2026)
Volleyball is a sport that requires technical skills, coordination, and good motor abilities. Mastery of basic techniques is a crucial factor in supporting overall playing performance, particularly the forearm pass, which serves as the initial step in building an attack as well as maintaining ball control against the opponent’s offense. This study aims to analyze the forearm passing movement skills of student-athletes based on the preparation, execution, and follow-through phases. This research employed a quantitative descriptive design, with Kinovea version 0.9.5 as the primary instrument for motion analysis. A total of 10 students were selected as research subjects through basic technique observation and joint angle measurement. The results show that 2 students (20%) fell into the “very accurate” category, 7 students (70%) into the “accurate” category, and 1 student (10%) into the “less accurate” category. Kinematic analysis recorded an average knee flexion angle of 106.96° (range 83°–132.9°) and an average shoulder extension angle of 97.05° (range 80.5°–123.2°), both of which fall within the effective range for supporting body stability and ball control. The findings indicate that mastery of basic techniques and good movement coordination significantly contribute to successful forearm passing performance. Overall, these values fall within a range that supports effective execution of the forearm passing technique, suggesting that proper body positioning, fundamental skill proficiency, and coordinated movement play essential roles in determining the quality of students’ forearm passing skills.